Using Business Games to Carry Out Scientific Research - Pusanovsky de Barros, Felipe; Carino Bouzada, Marco Aurélio (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2020)
This work aims to demonstrate the feasibility of using the results of applications of a game of companies - BR-Log - for purposes of scientific research, through an example that statistically tests the relationships among the following variables that involve operations and Logistics activities : Financial results, Market share and Inventory levels.